The Creative Destruction of Management Buy-Outs - Hayle, David N (2009)
So, as we move forward post MBO without the original Entrepreneur at the helm it is acknowledged that we will face a great many challenges as we continue along the path leading towards longevity and continued success, for in essence we want to go from ‘Good to Great’ and become ‘Built to Last’. In common with other organisations in the same situation, to address these challenges we need to become both wily and innovative in a manner that we haven’t been in the past. The previous owner/leader has taken a substantial sum of money off the table (as a result of the MBO) and going forward is likely to be less driven than he was previously, spending less time in the business thereby creating somewhat of a void. In filling this void does an MBO transaction provide the organisation with a firm level version of the ‘creative destruction’ espoused by Schumpeter as being so essential to the development of new radical innovation? Are the management teams that led the MBO's the ‘New Men’ that Schumpeter noted were a prequel to innovation? The subject of this management report is therefore focused on the innovation challenges Small-Medium Enterprises face once the previous leader has exited (or virtually exited) the organisation, following a change of ownership (specifically via an MBO). In completing this study I propose to look in depth at a small number of organisations, the selection of which will be skewed towards identifying those that are directly comparably in terms of size, culture and characteristics to PJD. Given the size of this subject it is appropriate to refine the scope of this piece of work, accordingly, I will specifically focus on any changes that occurred in the fields of process innovation and team structure and their impact (if any) on the success of the organisation. In respect of the team aspect, I will look to identify changes as a direct result of the removal of the influence of the entrepreneur and endeavor to determine whether the management teams are indeed Schumpeter’s ‘New Men’.